Cadophora arctica (Ploettnerulaceae, Helotiales), a new species from Franz Josef Land - Iliushin, Vadim A.; Kirtsideli, Irina Y.; Pankova, Inna G. (Phytotaxa, 2024)
A novel species in genus Cadophora is described as Cadophora arctica. The new species was isolated from, Franz Josef Land, Russia and is represented by ex-type strain VKM F-5011. To characterize the species, we used a polyphasic taxonomic approach. A description based on morphological characters is given and it is shown that the new species is morphologically different from closely related species (to C. caespitosa, C. fastigiata, C. melinii and C. rotunda). Partial sequences of internal transcribed spacer rDNA region (ITS1-5.8S-ITS2), D1/D2 region of 28S rDNA (LSU), the loci encoding β-tubulin (BenA) and partial translation elongation factor 1-α gene (TEF1) were analyzed as well. Sequences data, macro- and micromorphological characteristics distinguish C. arctica from all known species in genus Cadophora. C. arctica, isolated from Arctic drift wood, is able to grow at 2°C and is considered a psychrotolerant species.